Empowerment of Statue and Tapel Crafts Business Groups in Batuan Village, Sukawati-Gianyar - Amlayasa Anak Agung Bagus; A.A. Ayu Erna Trisnadewi; Desak Gde Dwi Arini (Community Service Journal of Law, 2024)
Creative industries in Batuan-Sukawati area has long been known and has good quality. One of them is the creative industry of statues and tapels. Balinese tapel’s are made of wood. The types of wood that are usually used as materials for making tapels include sandat and pule wood. To reduce the spooky feeling, the wood used is Sandat Wood and does not use Pule wood. This wood raw material must be brought in from other areas, because the wood in Batuan Village has been greatly reduced and can no longer meet production capacity and market demand. The results of field observations found several problems faced by partners. Partners often have difficulty in determining cash inflows and outflows accurately. The transaction recording process is still done manually or is still very simple so that the level of accuracy and effectiveness of transaction calculations is inadequate, and the level of efficiency of bookkeeping time is still relatively low, and partners do not yet have a business license. The solution provided is socialization in the form of literacy and assistance in business licensing as well as training in recording transactions and preparing simple financial reports. The results of community service activities are in the form of compiling practical guidelines for recording financial transactions that are clear and easy to follow, so that partners can record cash flow more accurately and efficiently. In addition, partners gain knowledge about the importance of having a business license.